Simultaneous changes of nuclear and magnetic structures across the morphotropic phase boundary in (1-x) BiFeO3 - XPbTiO3 - Bhattacharjee S.; Senyshyn A.; Krishna P.S.R.; Fuess H.; Pandey D. (My University, 2025)
We present here the results of a powder neutron diffraction study on the (1-x) BiFeO3 - xPbTiO3 (BF-xPT) system, which reveal an abrupt change in magnetic structure from a noncollinear antiferromagnetic one to a collinear G -type antiferromagnetic as the nuclear structure of the ferroelectric phase changes from monoclinic in Cc space group for x≤0.27 to tetragonal in P4mm space group for x≥0.31 across the morphotropic phase boundary (MPB). This reflects the multiferroic character of the MPB in the BF-xPT system. © 2010 American Institute of Physics.